Taxonomy of Micronectidae (Heteroptera: Nepomorpha) from Vietnam, with descriptions of 11 new species - Ha, Tuyet Ngan; Tran, Anh Duc (European Journal of Taxonomy, 2021)
The taxonomy of Micronectidae in Vietnam is reviewed. Based on our cumulative collections during 2001–2020, 11 new species of Micronecta Kirkaldy, 1897 are documented and described in this study: M. acuminata sp. nov., M. arcuata sp. nov., M. caperata sp. nov., M. clavata sp. nov., M. cultellata sp. nov., M. fulvopicta sp. nov., M. nieseri sp. nov., M. pingae sp. nov., M. sinuata sp. nov., M. undulata sp. nov., and M. vietnamica sp. nov. Nine species are recorded from Vietnam for the first time: M. decorata Lundblad, 1933, M. drepani Nieser, 2000, M. erythra Nieser, Chen & Yang, 2005, M. fugitans Breddin, 1905, M. johorensis Fernando, 1964, M. melanochroa Nieser, Chen & Yang, 2005, M. ornitheia Nieser, Chen & Yang, 2005, M. sahlbergi (Jakovlev, 1881), and M. tuwanoni Nieser, Chen, Leksawasdi, Thanyakam & Duangsupa, 2004. Thus, in this study, two genera and 37 species of Micronectidae are now reported from Vietnam: Synaptonecta Lundblad, 1933 with only one species, S. issa (Distant, 1910), and Micronecta with 36 species. A key to all species occurring in Vietnam, subgeneric diagnoses, and a key to all current subgenera of Micronecta are provided.